Cosmas Vestitor's Ascetic-Physiological Fragment (CPG 8163) - Fernández, Tomás (2012)
This article provides a new edition of Cosmas Vestitor's ascetic-physiological fragment (CPG 8163), which was first edited in 1955 by Antoine Wenger. This is the only fragment by Cosmas to be extant in an anthology, and it is possibly authentic. The previous edition of it was based only on two witnesses of the text, and was riddled with inaccuracies. The aim of this paper is to remedy these shortcomings by collating afresh the manuscripts known to Wenger, along with eight new witnesses. Its goal is also to set Cosmas in his context, and to provide a translation and brief explanation of the fragment.